Pengaruh Konsentrasi Biokatalisator Cairan Rusip dalam Mereduksi Limbah Ikan menjadi Pupuk Organik Cair - Andri Kurniawan; Khalis Arrasiksycah; Denny Syaputra (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2023)
Rusip is known to contain fermenting microbes such as lactic acid bacteria, fungi, and yeast which are almost similar to EM4. The content of bacteria contained in rusip liquid has the potential to be used as a local biocatalyst, one of which is in reducing waste in the manufacture of liquid organic fertilizer. This study aimed to examine the potential of rusip as a biocatalyst by knowing its effect in reducing fish waste into liquid organic fertilizer with different concentrations. Fertilizer was made by fermenting 200 g of fish waste with a concentration of 30%, 40% and 50% rusip liquid for 7 days. As a control treatment, 40% EM4 was used because this treatment gave the best results in decomposing fish waste in the manufacture of POC from previous studies. The results showed that the concentration of the rusip liquid biocatalyst had an effect on reducing fish waste into liquid organic fertilizer. The highest reduced waste weight and liquid fertilizer volume were produced by the P3 treatment, namely 78.7 g and 67 ml. The lowest pH value was obtained by the control treatment of 4.73 and followed by the P3 treatment of 4.9. The highest nitrogen value was obtained from the P3 treatment of 0.77%. The most dominant fertilizer characteristic was produced by the P3 treatment which produced the same visual characteristics of the fertilizer as the control treatment.